Shear-induced reorganization of renal proximal tubule cell actin cytoskeleton and apical junctional complexes - Duan, Yi (National Academy of Sciences, 2008)
In this study, we demonstrate that fluid shear stress (FSS)-induced actin cytoskeletal reorganization and junctional formation in renal epithelial cells are nearly completely opposite the corresponding changes in vascular endothelial cells (ECs) [Thi MM et al. (2004) Proc Natl Acad Sci USA 101:16483–16488]. Mouse proximal tubule cells (PTCs) were subjected to 5 h of FSS (1 dyn/cm(2)) to investigate the dynamic responses of the cytoskeletal distribution of filamentous actin (F-actin), ZO-1, E-cadherin, vinculin, and paxillin to FSS. Immunofluorescence analysis revealed that FSS caused basal stress fiber disruption, more densely distributed peripheral actin bands (DPABs), and the formation of both tight junctions (TJs) and adherens junctions (AJs). A dramatic reinforcement of vinculin staining was found at the cell borders as well as the cell interior. These responses were abrogated by the actin-disrupting drug, cytochalasin D. To interpret these results, we propose a “junctional buttressing” model for PTCs in which FSS enables the DPABs, TJs, and AJs to become more tightly connected. In contrast, in the “bumper-car” model for ECs, all junctional connections were severely disrupted by FSS. This “junctional buttressing” model explains why a FSS of only 1/10 of that used in the EC study can cause a similarly dramatic, cytoskeletal response in these tall, cuboidal epithelial cells; and why junctional buttressing between adjacent cells may benefit renal epithelium in maximizing flow-activated, brush border-dependent, transcellular salt and water reabsorption.